Program Peningkatan Kompetensi Perusahaan di Era Digital dari FinTech - Laras Tiara Putri; Lulu Angelita; Agus Munandar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the digital era of FinTech, a company uses a program called a “corporate competency improvement program” to help digital-based businesses better meet the demands of increasingly digital customers. Likewise, the financial industry, cooperatives and second-hand goods stores continue to improve their quality. One program that can help a business improve the quality of its customer service is company digitalization. Businesses related to finance have been successful. However, there were several obstacles found in program implementation, for example an outdated IT framework, a work culture that had not been digitized, and poor coordination between internal organizational divisions.